Assessing factors that hinder effective utilisation of family planning services by perinatally HIV infected adolescents in Chiradzulu district - Siyasiya, Gloria (2021)
Adolescents who have perinatal HIV are equally sexually active and a higher proportion of them is becoming pregnant and bears children. This is happening when family planning services are being provided at the teen clubs where they access HIV services. The study aimed at assessing reasons why these adolescents are not utilizing the family planning services that are being offered. The objectives of the study were to: establish perinatally HIV infected adolescents’ knowledge of the importance of family planning, identify sexual and reproductive health services available for perinatally HIV adolescents, determine the support system that is available for perinatally HIV infected adolescents and determine the challenges that the perinatally HIV infected adolescents face during care.This qualitative study was conducted at Chiradzulu District Hospital and Namitambo Health Centre from March to May 2019. The researcher recruited19 adolescents aged 15-19 years, who were perinatally infected with HIV and were aware of their HIV status. The results showed that most perinatally HIV infected adolescents are aware of the importance of family planning. Additionally, it was found that misconceptions about and side effects of some family planning methods are the main reason for non-contraceptive use.Parents/guardians are the main source of support but they do not have adequate knowledge about reproductive health issues relating to the adolescents, hence fail to provide the needed support. The study also showed that the majority of the adolescents who have a romantic relationship disclosed their HIV status to their partners. The findings also revealed that there is to involve parents and traditional leaders in issues of sexual and reproductive health so that they know the kind of support they could provide to their adolescent children. Additionally, improving the sexual and reproductive health information and services for adolescents will help create contraceptive demand by these adolescents.